(untitled) (Jurnal Sosial Ekonomi Pertanian, 2023)
This study aims to analyze the relationship between product attributes and the purchase decision process for Juragan ground coffee products in Kubu Raya Regency. Respondents amounted to 50 people who were carried out by accidental sampling. The data analysis technique used is the Spearman rank test with SPSS 21 software. The results showed that the product attribute variables that had a relationship with the purchasing decision process of Juragan ground coffee products were product quality, packaging and price, while the brand had no relationship with the purchasing decision process of Juragan ground coffee products in Kubu Raya Regency. This means that more attractive packaging and having good product quality and affordable prices will make consumers make purchasing decisions for Juragan ground coffee products in Kubu Raya Regency.